Peramalan Harga Minyak Goreng di Provinsi Sulawesi Utara dengan Menggunakan Metode Analisis Autoregressive Integrated Moving Average (ARIMA) - Marsela Pangalila; Charles E. Mongi; Djoni Hatidja (Sam Ratulangi University, 2024)
Cooking oil is a basic ingredient that plays an important role in the Indonesian economy. Cooking oil is one of the nine basic commodities which plays an important role in the Indonesian economy. The data used for research is from the Agency Center for Statistics from January 2018 to December 2022 with the forecasting method used for this data, namely the Autoregressive Integrated Moving Average (ARIMA) time series method. This research aims to obtain the best time series model and to determine the results of forecasting cooking oil prices in North Sulawesi using the ARIMA method. The research results show that the best model obtained is the ARIMA model (1,2,1) with a Mean Square Error (MSE) of 350248. From the forecasting results it is found that the price of cooking oil has increased.